SISTEM PENDUKUNG KEPUTUSAN PERPANJANGAN KONTRAK KERJA KARYAWAN PADA PT. TELKOM AKSES REG IV MENGGUNAKAN METODE ORESTE - Saifur Rohman Cholil (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
PT Telkom Akses has fairly many employees, some of these employees still have status as contract employees, The employee's employment contract lasts for one year and then at the end of each period of the employee's contract there will be a performance evaluation which includes several criteria to determine whether the employee gets a contract extension or not. The number of employees of PT Telkom Akses with the status of contract employees is not small and the assessment process that is still manual becomes an obstacle in the assessment process because it is difficult and requires a lot of time. In determining employee work contracts, subjectivity often arises from managers or coworkers who can influence the decision making process regarding employee employment contracts. The criteria for evaluating employee work contracts include appraisal, absenteeism, BPJS employment, and employee position. The results of this study obtained a value of 0.90 on the validation of the Spearman Correlation Coefficient calculation. So the system is feasible to be used in the determination of employee employment contract at PT. Telkom Access REG IV.